1998
DOI: 10.1046/j.1360-0443.1998.931015117.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating measures of family history of alcoholism: density versus dichotomy

Abstract: FHD is a good candidate to be a standard FH measure because it is quantitative, based on familial relatedness and capable of accounting for significant variation in alcoholism diagnosis and two indices of alcoholism severity in men and in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
104
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 39 publications
2
104
0
1
Order By: Relevance
“…Individual risk for AUDs is further increased by having multiple fi rst-and second-degree relatives with alcoholism (Dawson et al, 1992), and children with high familial loading of alcoholism are at greater risk for early-onset drinking (Hill & Yuan, 1999). This suggests that familial loading of alcoholism is an important determinant of overall risk susceptibility, which is also supported by studies that have found relationships between this measure and variation in alcoholism diagnosis and severity (Stoltenberg et al, 1998). Family history density (FHD) of AUDs likely refl ects genetic loading risk, as scores for fi rst-and second-degree relatives with alcoholism are assigned based on genetic relatedness to offspring with familial alcoholism (Stoltenberg et al, 1998).…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Individual risk for AUDs is further increased by having multiple fi rst-and second-degree relatives with alcoholism (Dawson et al, 1992), and children with high familial loading of alcoholism are at greater risk for early-onset drinking (Hill & Yuan, 1999). This suggests that familial loading of alcoholism is an important determinant of overall risk susceptibility, which is also supported by studies that have found relationships between this measure and variation in alcoholism diagnosis and severity (Stoltenberg et al, 1998). Family history density (FHD) of AUDs likely refl ects genetic loading risk, as scores for fi rst-and second-degree relatives with alcoholism are assigned based on genetic relatedness to offspring with familial alcoholism (Stoltenberg et al, 1998).…”
supporting
confidence: 62%
“…This suggests that familial loading of alcoholism is an important determinant of overall risk susceptibility, which is also supported by studies that have found relationships between this measure and variation in alcoholism diagnosis and severity (Stoltenberg et al, 1998). Family history density (FHD) of AUDs likely refl ects genetic loading risk, as scores for fi rst-and second-degree relatives with alcoholism are assigned based on genetic relatedness to offspring with familial alcoholism (Stoltenberg et al, 1998). However, environmental contributions that infl uence risk may also be present, depending on the offspring's exposure to the relative(s) with AUD(s), which may also moderate risk vulnerability (Jacob et al, 2003).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…A 'family-history load' metric weighted AUD relatives according to the estimated shared genetic material (eg, first-degree 0.5, second-degree 0.25) and summed weighted scores for all AUD relatives (Stoltenberg et al, 1998) (Table 1).…”
Section: Participantsmentioning
confidence: 99%
“…Клиническим при-знаком генетической предрасположенности являет-ся семейная отягощенность -наличие среди кров-ных родственников больного случаев этого же забо-левания, своего рода «генетический груз». Логично полагать, что чем больше родственников индивиду-ума имели признаки наркологического заболева-ния, тем выше уровень предрасположенности и больше тяжесть «генетического груза» или степень (плотность) семейной отягощенности [17]. Имеются косвенные, часто не подтвержденные количествен-но, представления о связи семейной отягощенности по алкоголизму и небольшой длительности ремиссий [18].…”
unclassified